Clear band formation simulated by dislocation dynamics - Nogaret, T.; Rodney, D.; Fivel, M.; Robertson, C. (Вопросы атомной науки и техники, 2009)
Dislocation Dynamics simulations of dislocations gliding across a random populations of
Frank loops are presented. Specific local rules are developed to reproduce elementary interaction
mechanisms obtained in Molecular Dynamics simulations. It is shown that absorption of Frank
loops as helical turns on screw dislocations governs the process of clear band formation,
because: (1) it transforms the loops into jogs on dislocations, (2) when the dislocations unpin, the
jogs are transported along the dislocation lines, leading to a progressive clearing of the band and
(3) the dislocations are re-emitted in a glide plane different from the initial one, allowing for a
broadening of the band. It is also shown that a pile-up of dislocations is needed to form a clear
band of finite thickness. У термінах дислокаційної динаміки представлено моделювання дислокацій, що
перетинають розташовану випадковим чином сукупність петель Франка. Розроблені
локальні правила для відтворення елементарних механізмів взаємодії, що отримані при
моделюванні методом молекулярної динаміки. Показано, що поглинання петель Франка у
вигляді гелікоїдальних витків на гвинтових дислокаціях визначає процес утворення
вільних зон, оскільки: 1) воно перетворює петлі у східці на дислокаціях, 2) у випадку
відкріплення дислокації східці переносяться вздовж ліній дислокацій і 3) дислокації знову
надходять у площину ковзання, яка відрізняється від вихідної, забезпечуючи тим самим
розширення вільної зони. Крім того, показано, що скупчення дислокацій необхідне для
утворення вільної зони з кінцевою товщиною. В терминах дислокационной динамики представлено моделирование дислокаций,
пересекающих расположенную случайным образом совокупность петель Франка.
Разработаны локальные правила для воспроизведения элементарных механизмов
взаимодействия, полученных при моделировании методом молекулярной динамики.
Показано, что поглощение петель Франка в виде геликоидальных витков на винтовых
дислокациях определяет процесс образования свободных зон, поскольку: 1) оно
преобразует петли в ступеньки на дислокациях, 2) в случае открепления дислокации
ступеньки переносятся вдоль линий дислокаций и 3) дислокации вновь поступают в
плоскость скольжения, отличающуюся от исходной, обеспечивая тем самым расширение
свободной зоны. Кроме того, показано, что скопление дислокаций необходимо для
образования свободной зоны с конечной толщиной.